Self-assessment of amyotrophic lateral sclerosis functional rating scale on the patient’s smartphone proves to be non-inferior to clinic data capture - Steinfurth, Laura; Grehl, Torsten; Weyen, Ute; Kettemann, Dagmar; Steinbach, Robert; Rödiger, Annekathrin; Grosskreutz, Julian; Petri, Susanne; Boentert, Matthias; Weydt, Patrick; Bernsen, Sarah; Walter, Bertram; et al. (Amyotrophic lateral sclerosis & frontotemporal degeneration, 2025)
To investigate self-assessment of the amyotrophic lateral sclerosis functional rating scale-revised (ALSFRS-R) using the patient’s smartphone and to analyze non-inferiority to clinic assessment. In an observational study, ALSFRS-R data being remotely collected on a mobile application (App-ALSFRS-R) were compared to ALSFRS-R captured during clinic visits (clinic-ALSFRS-R). ALS progression rate (ALSPR)—as calculated by the monthly decline of ALSFRS-R—and its intrasubject variability (ALSPR-ISV) between ratings were used to compare both cohorts. To investigate non-inferiority of App-ALSFRS-R data, a non-inferiority margin was determined. A total of 691 ALS patients using the ALS-App and 1895 patients with clinic assessments were included. Clinical characteristics for the App-ALSFRS-R and clinic-ALSFRS-R cohorts were as follows: Mean age 60.45 (SD 10.43) and 63.69 (SD 11.30) years (p < 0.001), disease duration 38.7 (SD 37.68) and 56.75 (SD 54.34) months (p < 0.001) and ALSPR 0.72 and 0.59 (p < 0.001), respectively. A paired sample analysis of ALSPR-ISV was applicable for 398 patients with clinic as well as app assessments and did not show a significant difference (IQR 0.12 [CI 0.11, 0.14] vs 0.12 [CI 0.11, 0.14], p = 0.24; Cohen’s d = 0.06). CI of IQR for App-ALSFRS-R was below the predefined non-inferiority margin of 0.15 IQR, demonstrating non-inferiority. Patients using a mobile application for remote digital self-assessment of the ALSFRS-R revealed younger age, earlier disease course, and faster ALS progression. The finding of non-inferiority of App-ALSFRS-R assessments underscores, that data collection using the ALS-App on the patient’s smartphone can serve as additional source of ALSFRS-R in ALS research and clinical practice.